PENGEMBANGAN E-LKPD BERBASIS WORDWALL PADA MATERI MENGENAL KARA KTERISTIK DAN CIRI – CIRI FISIK LINGKUNGAN RUMAH DAN SEKOLAH DI SEKOLAH DASAR - Siti Fatimah Azzahra, Denira; Kurnia, Dadang; Destiana, Dita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The lack of availability of teaching materials that suit the needs of students, and the variety of tools and media in learning activities is still limited. The purpose is to determine the feasibility and response of students to the E-LKPD developed. The method used is Research and Development (R&D) with the ADDIE development model. The subject of this study is a second-grade student of SDN Ciawi 03. The data collection instrument was a validation questionnaire given to 3 validators, 1 material expert, 1 linguist, 1 media expert, and a student response questionnaire. The results of validation by experts obtained the feasibility that the Wordwall-based E-LKPD is 84% from material experts with the Valid category, the average from linguists is 100% with the Valid category, and the average acquisition from media experts is 93% with the Valid category. The results of the student's response to the Wordwall-based E-LKPD obtained 84% with the Valid category. Based on the overall data analysis results, it can be concluded that the Wordwall-based E-LKPD developed is declared Valid and can be used in learning activities.